Timing control in regulatory networks by multisite protein modifications - Salazar, Carlos; Brümmer, Anneke; Alberghina, Lilia; Höfer, Thomas (Trends in cell biology, 2010)
Computational and experimental studies have yielded quantitative insights into the role for multisite phosphorylation, and other protein modifications, in cell function. This work has emphasized the creation of thresholds and switches for cellular decisions. To date, the dynamics of phosphorylation events have been disregarded yet could be equally relevant for cell function. Here, we discuss theoretical predictions about the kinetic functions of multisite phosphorylation in regulatory networks and how these predictions relate to experimental findings. Using DNA replication as an example, we demonstrate that multisite phosphorylations can support coherent origin firing and robustness against rereplication. We suggest that multisite protein modifications provide a molecular mechanism to robustly time cellular events in the cell cycle, the circadian clock and signal transduction.